A resourceful tenth plan - Kurian, N.J.; Mishra, Rajiv (2003)
A distinguishing feature of the Tenth Plan is that is does not satisfy itself merely with growth induced percolation of benefits. The Tenth plan has set monitorable targets for raising human well being. Reduction of poverty ratio by 5 percentage points by 2007 and by 15 percentage points by 2012 is the most important monitorable target. Targets have also been set for providing gainful and high-quality employment and reflected in the goal of creating 50 million jobs. - Reproduced.
Keywords: Tenth Five Year Plan; Economic planning - India; Economic planning